2014
DOI: 10.1159/000360737
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Association between the COMT Val158Met Polymorphism and Openness to Experience in Panic Disorder Patients

Abstract: Background: Because major depression and panic disorder are both more prevalent among females and since several lines of evidence suggest that genetic factors might influence an individual's vulnerability to panic disorder, gene-gender interactions are being examined in such psychiatric disorders and mental traits. A number of studies have suggested that specific genes, e.g. catechol-O-methyltransferase (COMT), might lead to distinct clinical characteristics of panic disorder. Method: We compared gender-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Despite the lack of studies exploring a direct relationship between females’ hormonal cycling and the trait of Openness, there is evidence for its indirect modulation by estrogen. That is, the catechol- O -methyltransferase gene, which is associated with the trait of Openness (Konishi et al 2014), is influenced by estrogen (Harrison and Tunbridge 2008). We thus suggest that the influence of ovarian hormones on RSFC in the Rew network as well as on perceived Openness induces joint intra-individual variation (i.e., shared variance), which in turn increases the strength of the neural and phenotypical association across women.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of studies exploring a direct relationship between females’ hormonal cycling and the trait of Openness, there is evidence for its indirect modulation by estrogen. That is, the catechol- O -methyltransferase gene, which is associated with the trait of Openness (Konishi et al 2014), is influenced by estrogen (Harrison and Tunbridge 2008). We thus suggest that the influence of ovarian hormones on RSFC in the Rew network as well as on perceived Openness induces joint intra-individual variation (i.e., shared variance), which in turn increases the strength of the neural and phenotypical association across women.…”
Section: Discussionmentioning
confidence: 99%
“…For example, women diagnosed with many mental disorders (e.g., phobias, major depression, dysthymic disorder, generalized anxiety disorder, borderline personality disorder) were associated with neuroticism at a higher rate than men (Grossman and Wood, 1993 ). Although there were many previous researches supporting the difference in neuroticism between men and women(Foot and Koszycki, 2010 ; Banzhaf et al, 2012 ; Konishi et al, 2014 ), only when the latent structure are equivalent across gender, the observed gender difference in neuroticism can truly predict the true difference between males and females.…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, the COMT gene, located on chromosome 22q11.2 [Grossman, Emanuel, & Budarf, ], encodes COMT, which contributes to the inactivation of catecholamines including adrenaline, noradrenaline, and dopamine. The COMT gene val158met polymorphism was found to be related to many physical as well as psychological diseases such as schizophrenia, depressive disorder, bipolar disorder, attention deficit, and hyperactivity and obsessive compulsive disorders [Barnett, Jones, Robbins, & Muller, ; Cao et al, ; Diaz‐Asper et al, ; He et al, ; Jones et al, ; Konishi et al, ; Lachman, Nolan, Mohr, Saito, & Volavka, ; Liu et al, ; Massat et al, ; Melo‐Felippe et al, ; Qian et al, ; Sampaio et al, ; Seok et al, ; Shimada et al, ; Tukel et al, ; Villemonteix et al, ; Wagner et al, ; Watanabe et al, ; Zhang et al, ]. Val158met polymorphism exerts a significant effect on COMT enzyme activity; the Val allele is associated with high enzymatic activity resulting in lower prefrontal dopamine levels in vivo [Lachman et al, ].…”
Section: Introductionmentioning
confidence: 99%